Alveolar rhabdomyosarcoma confined to the bone marrow with no identifiable primary tumour using FDG-PET/CT. Issue 1 (December 2015) - Karagiannis, Panagiotis; Guth, Nina; Thoennissen, Gabriela; Bern, Christina; Sperveslage, Jan; Oschlies, Ilske; Bokemeyer, Carsten; Klapper, Wolfram; Wardelmann, Eva; Thoennissen, Nils
Abstract Background Rhabdomyosarcoma (RMS), a malignant tumour of mesenchymal origin which can occur at various sites in the body, is one of the most common soft tissue sarcomas in both children and adolescents, but is rare in adults with a prevalence of less than 1 %. The alveolar subtype of rhabdomyosarcoma (ARMS) is typically characterized by a specific reciprocal chromosomal translocation involving the PAX3 and FKHR or PAX7 and FKHR genes, respectively. ARMS is most frequently seen in childhood, and typically affects the sinuses and soft tissue of the extremities, with approximately 23 % exhibiting metastasis to the marrow. Non-invasive F-18-fluorodeoxyglucose positron-emission tomography (FDG-PET) scans have a high ability to detect lymph nodes, bone, and bone marrow involvement in patients with metastatic RMS, often with higher sensitivity and specificity compared with conventional modalities. Case presentation Here, we report an unusual case of ARMS confined to the bone marrow in an older adult that lacked an identifiable primary tumour using FDG-PET/CT and mimicked a haematological disease with pancytopenia but without abnormal findings by FDG-PET/CT. The patient was initially treated with topotecan/cyclophosphamide and subsequently switched to vinorelbine. Due to severe toxicity the treatment was discontinued, however after 7-months follow-up, the patient is still alive with an improved general state of health and only a mild pancytopenia with no need for blood transfusions. Conclusion Rhabdomyosarcoma can be limited to the bone marrow with no identifiable primary tumour. This case shows that the use of a bone marrow biopsy in suspected malignancies affecting the bone marrow is irreplaceable.